Dampak Sertifikasi Halal Terhadap Penjualan Produk Makanan UMKM (Studi Kasus Pada UMKM di Kalibata): indonesian - Fitriyadi Omamoy; Muhammad Tho’in; Sumadi (ITB AAS INDONESIA Surakarta, 2026)
This study aims to analyze the impact of halal certification on increasing sales of food products among Micro, Small, and Medium Enterprises (MSMEs), with a case study in Kalibata. Halal certification is considered a crucial factor in building consumer trust, particularly in Indonesia, where most of the population is Muslim, and a strategic tool for expanding market share. The research employs a quantitative approach, with data collected through questionnaires distributed to MSME actors in the Kalibata area. The data were analyzed using statistical techniques to examine the relationship between halal certification ownership and changes in sales levels. The results indicate that MSMEs with halal certification experience a significant increase in sales compared to those without certification. This finding suggests that halal certification not only serves as a guarantee of compliance with Islamic law but also functions as an effective marketing tool to enhance product competitiveness in the market. The implications of this study highlight the importance of government and related institutions in facilitating access, providing education, and supporting the halal certification process for MSMEs. Such efforts are expected to promote local economic growth and improve the sustainable competitiveness of MSME products.